T‐cell responses after haematopoietic stem cell transplantation for aggressive relapsing–remitting multiple sclerosis. Issue 2 (12th September 2013) - Burman, Joachim; Fransson, Moa; Tötterman, Thomas H.; Fagius, Jan; Mangsbo, Sara M.; Loskog, Angelica S. I.
Summary Autologous haematopoietic stem cell transplantation (HSCT) for relapsing–remitting multiple sclerosis is a potentially curative treatment, which can give rise to long‐term disease remission. However, the mode of action is not yet fully understood. The aim of the study was to evaluate similarities and differences of the CD4+ T‐cell populations between HSCT‐treated patients (n = 12) and healthy controls (n = 9). Phenotyping of memory T cells, regulatory T (Treg) cells and T helper type 1 (Th1) and type 17 (Th17) cells was performed. Further, T‐cell reactivity to a tentative antigen, myelin oligodendrocyte glycoprotein, was investigated in these patient populations. Patients treated with natalizumab (n = 15) were included as a comparative group. White blood cells were analysed with flow cytometry and T‐cell culture supernatants were analysed with magnetic bead panel immunoassays. HSCT‐treated patients had similar levels of Treg cells and of Th1 and Th17 cells as healthy subjects, whereas natalizumab‐treated patients had lower frequencies of Treg cells, and higher frequencies of Th1 and Th17 cells. Cells from HSCT‐treated patients cultured with overlapping peptides from myelin oligodendrocyte glycoprotein produced more transforming growth factor‐β1 than natalizumab‐treated patients, which suggests a suppressive response. Conversely, T cells from natalizumab‐treated patients cultured with those peptides produced more interleukin‐17 (IL‐17), IL‐1 and IL‐10, indicating a Th17 response. In conclusion, we demonstrate circumstantial evidence for the removal of autoreactive T‐cell clones as well as development of tolerance after HSCT. These results parallel the long‐term disease remission seen after HSCT.